On the improvement of SPT2 approach in the theory of a hard sphere fluid in disordered porous media - Holovko, M.; Patsahan, T.; Dong, W. (Condensed Matter Physics, 2017)
The SPT2 approach is based on the scaled particle theory and developed for the description of thermodynamic
properties of hard sphere (HS) fluids in disordered porous media. Using this approach a porous medium is
modelled as a quenched matrix of hard spheres (HS) or overlapping hard spheres (OHS). A hard sphere fluid
immersed in a matrix can move in a void between matrix particles. A number of approximations were previously
proposed within the SPT2 approach. Among these approximations, the SPT2b1 has been considered as the most
successful and accurate one in a large range of fluid densities and for different matrix parameters. However, at
high densities, it can lack accuracy, since it does not take into account that the maximum packing fraction of a
HS fluid in a matrix is limited, not by the geometrical porosity of a matrix φ0 and the probe particle porosity φ,
but by another type of porosity φ
∗
introduced in our previous studies. The porosity φ
∗
is related to the maximal
adsorption capacity of a matrix and it is lower than φ0 and larger than φ. This can be crucial for a fluid in matrices
of low porosities and at high fluid density, especially in the region near close-packing conditions. Therefore,
the approximations SPT2b2 and SPT2b3 taking into account this feature were suggested, although they still
needed a correction because of their poor accuracy. In the present study, we improved the versions of these
approximations, named as SPT2b2∗
and SPT2b3∗
. We compare these different approximations with the results
of computer simulations performed in the Monte Carlo grand-canonical ensemble. We test the SPT2 approach
both for the one- and three-dimensional cases. We show that the SPT2b3∗ provides a very good description of
the chemical potential of a confined fluid, which is better than others. This extends the applicability of the SPT2
approach to the studies of very dense fluids confined in disordered matrices. Пiдхiд SPT2 базується на теорiї масштабної частинки i розроблений для опису термодинамiчних властивостей твердокулькового (HS) плину в невпорядкованих пористих середовищах. При використаннi цього
пiдходу пористе середовище моделюється як заморожена матриця твердих кульок (HS) або твердих кульок, якi перетинаються (OHS). Твердокульковий плин, помiщений в матрицю, може рухатися у вiльному
просторi помiж матричними частинками. Ранiше ряд наближень було запропоновано в рамках пiдходу
SPT2. Серед цих наближень вважалося, що SPT2b1 є найбiльш успiшним i точним у широкiй областi густин плину i рiзних параметрiв матрицi. Проте, при високих густинах точнiсть може бути недостатньою,
оскiльки цей пiдхiд не бере до уваги те, що максимальна упаковка твердокулькового плину в матрицi є
обмеженою не тiльки геометричною пористiстю матрицi φ0 i пористiстю пробної частинки φ, але й ще
одним типом пористостi φ
∗
, який був запропонований нами в попереднiх дослiдженнях. Пористiсть φ
∗
пов’язана iз максимальною адсорбцiйною ємнiстю матрицi, i вона є меншою нiж φ0 та бiльшою нiж φ. Вона може бути визначальною для плину в матрицях iз низькою пористiстю та при високих густинах плину,
особливо в областi близькiй до щiльної упаковки. Тому було запропоновано наближення SPT2b2 i SPT2b3,
що враховують цю властивiсть, хоча й вони все ще потребували удосконалення у зв’язку iз їх поганою
точнiстю. В даному дослiдженнi ми покращуємо цi наближення i назвали їх SPT2b2∗
та SPT2b3∗
. Ми порiвнюємо цi наближення iз результатами комп’ютерного моделювання, яке проводилося за допомогою
методу Монте-Карло у великому канонiчному ансамблi. Перевiрено пiдхiд SPT2 для одно- i тривимiрних
випадкiв. Показано, що SPT2b3∗
забезпечує дуже добрий опис, який є кращий за iншi, для хiмiчного потенцiалу плину в просторовому обмеженнi. Це розширює область застосування пiдходу SPT2 на випадок
вивчення дуже щiльних систем плину в невпорядкованих матрицях.